Antibiotic treatment durations for common infectious diseases in Switzerland: comparison between real-life and local and international guideline recommendations. (March 2023) - Schaub, Cédéric; Barnsteiner, Stefanie; Schönenberg, Ladina; Bloch, Nando; Dräger, Sarah; Albrich, Werner C.; Conen, Anna; Osthoff, Michael
Highlights: Antibiotic treatment duration was assessed in pneumonia, cellulitis, and cholangitis. Treatment duration in the three hospitals exceeded recommendations in > 30%. Post-discharge treatment contributed significantly to the prolonged duration. Substantial opportunities exist to improve antibiotic prescribing in Switzerland. ABSTRACT: Objectives: Shortening the duration of antibiotic therapy (DAT) for common infectious diseases may be an effective strategy to tackle antimicrobial resistance. Shorter DAT has been proven safe and effective for community-acquired pneumonia (CAP), cellulitis, and cholangitis. Methods: In a retrospective multicentre quality-control study, medical records of 770 patients hospitalized with CAP, cellulitis, and cholangitis at three tertiary care hospitals in Switzerland during 2017–2018 were randomly selected. Appropriateness of antibiotic treatment duration was assessed according to international and local guidelines. Results: Records of 271, 260, and 239 patients with CAP, cellulitis, and cholangitis were included, respectively. Median DAT was seven days (interquartile range [IQR] 6–9), ten days (IQR 8–13), and nine days (IQR 6–13) in CAP, cellulitis, and cholangitis, respectively. DAT longer than recommended by local and international guidelines was observed in 32% and 37% of CAP patients, 23% and 70% of cellulitis patients, and 33% and 37% of cholangitis patients, respectively. Positive blood cultures (odds ratio [OR] = 2.42 (95% confidence interval [CI] 1.33–4.34]), infectious diseases consultation (OR = 1.79 [95% CI 1.05–2.78]), impaired renal function (OR = 0.99 [95% CI 0.98–1.00] per 1 ml/min / 1.73 m 2 increase in estimated glomerular filtration rate) and a higher degree of inflammation on admission (OR = 1.0 [95% CI 1.001–1.005] per 10 mg/L increase in C-reactive protein) were independently associated with a DAT longer than recommended in international guidelines. Conclusions: DAT exceeded recommendations in a significant proportion of patients with mostly community-acquired infections.